FACTORS ASSOCIATED WITH SEXUAL VIOLENCE AGAINST WOMEN: ANALYSIS OF POLICE REPORTS - Cristiane Lopes Amarijo; Daniele Ferreira Acosta; Camila Daiane Silva; Vera Lúcia de Oliveira Gomes (Universidade Federal do Paraná, 2014)
A documentary, quantitative and exploratory-descriptive study. It aimed to understand the profile of the victims and the aggressors and to characterize sexual violence registered in a Women's Police Station from August/2009 to December/2011. The collected data were entered into Microsoft Excel® spreadsheets and analysed by means of descriptive statistics and absolute and relative numbers. Among the 39 cases analyzed, there was a prevalence of victims with ages ranging from 20 to 30 years old, white, elementary education and with paid employment. Violence committed by unknown men prevailed, 30-40 years old, white, elementary education and construction workers. Physical force was the most used intimidation form to commit rape, and the public roads were the main scenario. Most of the victims were submitted to forensic examination. Many cultural aspects, beliefs and values interfere or inhibit the reporting of such crimes. It is nursing's responsibility to act both in health promotion and recovery of the victims, including preventive actions.